Genotype-by-environment interaction and tolerance of tropical maize under low nitrogen conditions - DEDY SUPRIADI; YUSUF MUFTI BIMANTARA; YUNIEL MELVANOLO ZENDRATO; EKO WIDARYANTO; KUSWANTO KUSWANTO; BUDI WALUYO (Society for Indonesian Biodiversity, 2025)
Abstract. Supriadi D, Bimantara YM, Zendrato YM, Widaryanto E, Kuswanto K, Waluyo B. 2025. Genotype-by-environment interaction and tolerance of tropical maize under low nitrogen conditions. Biodiversitas 26: 3863-3874. The environment is the main factor affecting the performance of agronomy and the yield of tropical maize. In this context, the development of maize hybrids with low nitrogen (N) tolerance is crucial but challenging since genotype selection is biased toward the existence of Genotypes by Environment Interaction (GEI). Therefore, this research aimed to show the responses as well as determine the tolerance and stability of maize hybrids under low nitrogen environmental conditions in four environments. A total of 10 maize hybrids were analyzed using a randomized complete block design with three replications. The results showed that GEI was significant for most of the observed traits, including grain yield and yield components, as well as physiological traits. The percentage of G × E variance exhibited considerable differences among various traits, with values ranging from 13.68% for stomatal length to 50.00% for the number of ear rows. The low nitrogen environment significantly influenced ear performance and physiological traits, resulting in a lower average grain yield (6.98 t ha-1) compared to normal conditions (10.72 t ha-1), as well as the other traits. G01, G02, and G05 were identified as tolerant hybrids based on the ranking summary of stress tolerance indices. Meanwhile, G01 and G03 were selected as stable hybrids based on stability statistics and Genotype + Genotype × Environment (GGE). G01 (R0211) had the highest yield and remained stable-tolerant in low-nitrogen environments, demonstrating its superiority as a genotype. This study and the above genotypes could be used as genetic material for future maize breeding to develop new varieties that are both high-yielding and stable under low N, especially under tropical regions.